A time domain random flicker band-limited Gaussian noise jamming algorithm for LMS-based GPS - Wu, Tao; Wu, Jixiang; Wang, Hui; Cui, Ligang; Yang, Yinsong (MATEC web of conferences, 2021)
Global position systems (GPS) receiver based on least mean square (LMS) could resist the interference by null jamming direction. Considering that the existing band-limited Gaussian noise jamming signals were easily suppressed by LMS-based GPS receivers, a time domain random flicker band-limited Gaussian noise jamming algorithm was proposed to improve its performance. By disturbing the convergence of LMS, it could achieve the purpose of suppressing the LMS-based GPS. Simulation result shows that the proposed algorithm has an average performance gain of 2.7dB~4.6dB under different number of interferences compared with band-limited Gaussian noise.